The Stars in the Sky and on the Globe: ʿAbd al-Raḥmān ibn ʿUmar al-Ṣūfī’s Visualization of the Heavens - Brentjes, Sonja (Aestimatio, 2021)
In this paper, I analyze about 50 manuscript copies of ʿAbd al-Raḥmān ibn ʿUmar al-Ṣūfī’s Book of the Images of the Stars (Kitāb ṣuwar al-kawākib althābita). I investigate how the constellations were visualized in those copies, what their changes tell us about the contexts in which Ṣūfī’s book was used, and which iconographic model dominated the transmission.